(untitled) (Journal of Engineering, 2009)
A PID controller satellite attitude yaw-axis control system was designed to step the angle of the satellite body via actuating a precise angular position of a DC motor as quickly and accurately as most optimally possible. The (PID) controller was advantageously chosen for its quick transient response and zero steady-state error. A mathematical model has been derived for the whole satellite attitude yaw-axis control system. Then, the computation power of the MATLAB is utilized to obtain a generalized optimal controller design that enables the satellite attitude yaw-axis control system to have the quickest settling time without excessive overshoot and zero steady state error.